Diagnosis of Li‐Fraumeni Syndrome: Differentiating TP53 germline mutations from clonal hematopoiesis: Results of the observational AGO‐TR1 trial. Issue 12 (3rd October 2018) - Weber‐Lassalle, Konstantin; Harter, Philipp; Hauke, Jan; Ernst, Corinna; Kommoss, Stefan; Marmé, Frederik; Weber‐Lassalle, Nana; Prieske, Katharina; Dietrich, Dimo; Borde, Julika; Pohl‐Rescigno, Esther; Reuss, Alexander; et al.
Abstract: The Li‐Fraumeni cancer predisposition syndrome (LFS1) presents with a variety of tumor types and the TP53 gene is covered by most diagnostic cancer gene panels. We demonstrate that deleterious TP53 variants identified in blood‐derived DNA of 523 patients with ovarian cancer (AGO‐TR1 trial) were not causal for the patients' ovarian cancer in three out of six TP53‐positive cases. In three out of six patients, deleterious TP53 mutations were identified with low variant fractions in blood‐derived DNA but not in the tumor of the patient seeking advice. The analysis of the TP53 and PPM1D genes, both intimately involved in chemotherapy‐induced and/or age‐related clonal hematopoiesis (CH), in 523 patients and 1, 053 age‐matched female control individuals revealed that CH represents a frequent event following chemotherapy, affecting 26 of the 523 patients enrolled (5.0%). Considering that TP53 mutations may arise from chemotherapy‐induced CH, our findings help to avoid false‐positive genetic diagnoses of LFS1. Abstract : We demonstrate that deleterious TP53 variants identified in blood‐derived DNA of 523 patients with ovarian cancer (AGO‐TR1 trial; NCT02222883) were not causal for the patients' ovarian cancer in 3 of 6 TP53‐positive patients. The analysis of the TP53 and PPM1D genes, both intimately involved in chemotherapy‐induced and/or age‐related clonal hematopoiesis, in all patients and 1, 053 age‐matched female control individuals revealed that clonal hematopoiesis represents a frequent event following chemotherapy, affecting 26 of the 523 patients enrolled (5.0%). Considering that TP53 mutations may arise from chemotherapy‐induced clonal hematopoiesis, our findings help to avoid false‐positive genetic diagnoses of Li‐Fraumeni Syndrome.